Atmospheric transport of hydrogen sulfide from proposed geothermal power plant (unit 18): predictions by physical modeling in a wind tunnel - Petersen, Ronald L., author; Cermak, Jack E., author; Fluid Dynamics and Diffusion Laboratory, Fluid Mechanics and Wind Engineering Program, Colorado State University, publisher (Colorado State University. Libraries, 1977)
Tests were conducted in the Colorado State University environmental wind tunnel facility of the transport and dispersion of the H2S plume emanating from a cooling tower (Unit 18) positioned at two locations near Anderson Springs, California. The wind tunnel tests were conducted with a cooling tower and terrain modeled to a scale of 1:1920. The effects of wind direction and wind speed upon the groundlevel H2S concentrations in the vicinity of Anderson Springs were established. Data obtained include photographs and motion pictures of smoke plume trajectories and ground-level tracer gas concentrations downwind of the cooling tower.
CER77-78JEC-RLP3.
Prepared for Pacific Gas and Electric Company.
September 1977.
Keywords: Geothermal power plants -- Environmental aspects -- California -- Lake County; Wind tunnel models; Hydrogen sulfide; Atmospheric diffusion -- Mathematical models